Analisis Timbulan Emisi Karbon Dioksida Area Kampus UPN “Veteran” Jawa Timur - Ramadhan, Firza; Purnomo, Yayok Suryo; Jawwad, Muhammad Abdus Salam (Jurnal Serambi Engineering, 2025)
The green space in the UPN Veteran campus area in East Java is a campus effort to control carbon dioxide (CO2) emissions generated by campus activities. Green spaces can absorb and store CO2 and convert it into energy and O2 through photosynthesis. The results showed that the CO2 emissions generated by the use of motorised vehicles, human respiration activities and the use of LPG energy at the research site amounted to 7,317,565.6 kgCO2/year. The total carbon uptake of the study area was 13,422,291 kgCO2/year. From the comparison between the total carbon dioxide (CO2) absorption and the generation of carbon dioxide (CO2) emissions at the research site, it is known that Green Space can absorb or reduce CO2 emissions as a whole.